Community structure of insect herbivores is driven by conservatism, escalation and divergence of defensive traits in Ficus - Martin Volf; Simon T. Segar; Scott E.Miller Brus Isua; Mentap Sisol; Gibson Aubona; Petr Simek; Martin Moos; Juuso Laitila; Jorma Kim; Jan Zima Jr; Jadranka Rota; George D. Weiblen; et al. (WILEY, 2022)
Escalation (macroevolutionary increase) or divergence (disparity between relatives) in trait values are two frequent outcomes of the plant‐herbivore arms race. We studied the defences and caterpillars associated with 21 sympatric New Guinean figs. Herbivore generalists were concentrated on hosts with low protease and oxidative activity. The distribution of specialists correlated with phylogeny, protease and trichomes. Additionally, highly specialised Asota moths used alkaloid rich plants. The evolution of proteases was conserved, alkaloid diversity has escalated across the studied species, oxidative activity has escalated within one clade, and trichomes have diverged across the phylogeny. Herbivore specificity correlated with their response to host defences: escalating traits largely affected generalists and divergent traits specialists; but the effect of escalating traits on extreme specialists was positive. In turn, the evolution of defences in Ficus can be driven towards both escalation and divergence in individual traits, in combination providing protection against a broad spectrum of herbivores.